Arrestin‐Domain Containing Protein 1 (Arrdc1) Regulates the Protein Cargo and Release of Extracellular Vesicles. Issue 17 (20th August 2018) - Anand, Sushma; Foot, Natalie; Ang, Ching‐Seng; Gembus, Kelly M.; Keerthikumar, Shivakumar; Adda, Christopher G.; Mathivanan, Suresh; Kumar, Sharad
Abstract: Extracellular vesicles (EVs) are lipid‐bilayered vesicles that are released by multiple cell types and contain nucleic acids and proteins. Very little is known about how the cargo is packaged into EVs. Ubiquitination of proteins is a key posttranslational modification that regulates protein stability and trafficking to subcellular compartments including EVs. Recently, arrestin‐domain containing protein 1 (Arrdc1), an adaptor for the Nedd4 family of ubiquitin ligases, has been implicated in the release of ectosomes, a subtype of EV that buds from the plasma membrane. However, it is currently unknown whether Arrdc1 can regulate the release of exosomes, a class of EVs that are derived endocytically. Furthermore, it is unclear whether Arrdc1 can regulate the sorting of protein cargo into the EVs. Exosomes and ectosomes are isolated from mouse embryonic fibroblasts isolated from wild type and Arrdc1‐deficient ( Arrdc1 −/− ) mice. Nanoparticle tracking analysis–based EV quantitation shows that Arrdc1 regulates the release of both exosomes and ectosomes. Proteomic analysis highlights the change in protein cargo in EVs upon deletion of Arrdc1. Functional enrichment analysis reveals the enrichment of mitochondrial proteins in ectosomes, while proteins implicated in apoptotic cleavage of cell adhesion proteins and formation of cornified envelope are significantly depleted in exosomes upon knockout of Arrdc1.